Factors associating with surgical site infection following operative management of malleolar fractures at an urban level 1 trauma center. Issue 2 (6th June 2020) - Rascoe, Alexander S.; Kavanagh, Michael D.; Audet, Megan A.; Hu, Emily; Vallier, Heather A.
Abstract: Objectives: To identify comorbidities and injury characteristics associated with surgical site infection (SSI) following internal fixation of malleolar fractures in an urban level 1 trauma setting. Design: Retrospective. Setting: Level 1 trauma center. Patients/Participants: Seven-hundred seventy-six consecutive patients with operatively managed malleolar fractures from 2006 to 2016. Intervention: Open reduction internal fixation. Main Outcome Measurements: Superficial SSI (erythema and drainage treated with oral antibiotics and wound care) or deep SSI (treated with surgical debridement and antibiotics). Results: Fifty-six (7.2%) patients developed SSI, with 17 (30%) of these being deep infections. An a-priori power analysis of n = 325 (α=0.05, β=0.2) was tabulated for differences in univariate analysis. Univariate analysis identified categorical associations ( P  < .05) between SSI and diabetes mellitus, drug abuse, open fracture, and renal disease but not tobacco abuse, body mass index, or neuropathy. Multivariate logistic regression identified categorical associations between diabetes (OR = 2.2, 95% CI: 1.1–4.3), drug abuse (OR = 3.9, 95% CI: 1.2–12.7), open fracture (OR = 4.1, 95% CI: 1.3–12.8), and renal disease (OR = 2.7, 95% CI: 1.4–5.0) and any (superficial or deep) SSI. A separate multivariate logistic regression analysis found categorical associations between deep SSI requiring reoperation and diabetes (OR = 4.4, 95% CI: 1.6–12.2) and open fracture (OR = 4.1, 95% CI: 1.3–12.8). Furthermore, American society of anesthesiologists classification (ASA) Class 4 patients were (OR = 9.2, 95% CI: 2.0–41.79) more likely to experience an SSI than ASA Class 1 patients. Conclusions: Factors associated with SSI following malleolar fracture surgery in a single urban level 1 trauma center included diabetes, drug abuse, renal disease, and open fracture. The presence of diabetes or open type fractures were associated with deep SSI requiring reoperation. Level of Evidence: Level 3 prognostic: retrospective cohort study.